Adsorptive removal of methylene blue from aquatic environments using thiourea-modified poly(acrylonitrile-co-acrylic acid) - Adeyi, Abel Adekanmi; Md. Jamil, Siti Nurul Ain; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw; Lau, Kia Li; Abdullah, Mohammad (MDPI, 2019)
The paper evaluates the adsorptive potential of thiourea-modified poly(acrylonitrile-co-acrylic acid), (TA-poly(AN-co-AA)) for the uptake of cationic methylene blue (MB) from aquatic environments via a batch system. TA-poly(AN-co-AA) polymer was synthesized through redox polymerization and modified with thiourea (TA) where thioamide groups were introduced to the surface. Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), CHNS and Zetasizer were used to characterize the physico-chemical and morphological properties of prepared TA-poly(AN-co-AA). Afterwards, it was confirmed that incorporation of thioamide groups was successful. The adsorption kinetics and equilibrium adsorption data were best described, respectively, by a pseudo-second-order model and Freundlich model. Thermodynamic analysis showed the exothermic and spontaneous nature of MB uptake by TA-poly(AN-co-AA). The developed TA-poly(AN-co-AA) polymer demonstrated efficient separation of MB dye from the aqueous solution and maintained maximum adsorption capacity after five regeneration cycles. The findings of this study suggested that synthesized TA-poly(AN-co-AA) can be applied successfully to remove cationic dyes from aquatic environments.